Gone for good? Determinants of school dropout in Southern Italy - Niall O'Higgins; Marcello D'Amato; Floro Ernesto Caroleo; Adriana Barone (Institute for the Study of Labor (IZA), 2008)
The aim of the present paper is to gain some insight into the causes of dropping out of school and, more generally, of the factors that induce parents to review their choices about their child's schooling careers. To this end we apply to data from a school dropout survey insights from a model of sequential decision making by parents, where the initial decision can be reviewed in the light of new information emerging about the ability and opportunities of the child in benefitting from education relative to her outside (in the unskilled market). Analysis of the data confirms the role of both economic capacity (opportunity costs) and cultural capacity (ability to disentangle signals about future opportunities) of the family of origin shape observed choices about drop-out and return to school by individuals in our sample. Dropping out behaviour also appears to be strongly influenced by mismatches between school and student, however, and many of those who leave are not gone for good.
Keywords: I21; 370; Young people; school dropout; human capital; Abbrecher; Bildungsverhalten; Italien (Süd)